HuoXue JieDu formula improves diabetic retinopathy in rats by regulating microRNAs. (25th March 2021) - Li, Hong-li; Hao, Gai-mei; Tang, Shi-jie; Sun, Hui-hui; Fang, Yong-sheng; Pang, Xinxin; Liu, Hanying; Ji, Qingxuan; Wang, Xi-rui; Tian, Jing-yun; Jiang, Kun-xiu; Song, Xing-zhuo; et al.
Abstract: Ethnopharmacological relevance: HuoXue JieDu Formula (HXJDF) originates from classical formulas and was formed based on clinical experience. It is composed of Euonymus alatus (Thunb.) Siebold, Panax notoginseng (Burkill) F.H. Chen, the roots of Anguina kirilowii (Maxim.) Kuntze, and Coptis omeiensis (C. Chen) C.Y.Cheng . HXJDF prevents the deterioration of diabetic retinopathy. Aim of the study: To evaluate the effects of HXJDF on diabetic retinopathy in rats and investigate the roles of miRNAs in the effects of HXJDF. Materials and methods: A single intraperitoneal injection of streptozotocin (STZ) (65 mg/kg) was used to induce diabetes in rats. Rats were divided into three groups: normal, diabetic, and diabetic + HXJDF. Rats were treated with HXJDF (15.4 g/kg) or water by oral gavage for twelve weeks. At the end of the treatment, rats were anaesthetized, and retinal haemodynamic changes were measured. Then, the retinas were removed and examined by haematoxylin and eosin (HE) staining and TUNEL assays. In addition, miRNA expression profiling was performed using miRNA microarrays and further validated by quantitative real-time PCR (qRT-PCR). Results: Diabetes reduced peak systolic velocity (PSV), end-diastolic velocity (EDV), mean velocity (MV) and central retinal vein velocity (CRV) but increased the resistance index (RI) and pulsatility index (PI). In addition, in the diabetic group, retinal cell arrangement was disordered and loosely arranged, the retinal thickness and retinal ganglion cell (RGC) number decreased, and retinal cell apoptosis increased. In addition, 11 miRNAs were upregulated and 4 miRNAs were downregulated. After treatment, HXJDF improved retinal haemodynamics and morphologic changes, restored retinal thickness and RGC number and decreased retinal cell apoptosis. Furthermore, the changes in miRNA expression were significantly abolished by HXJDF. Conclusion: HXJDF may prevent DR by regulating the expression of miRNAs. Graphical abstract: Image 1